Regulation of protein turnover by heat shock proteins - YILMAZ, BETÜL; KARTAL ÖZER, NESRİN (ELSEVIER SCIENCE INC, 2014)
Protein turnover reflects the balance between synthesis and degradation of proteins, and it is a crucial process for the maintenance of the cellular protein pool. The folding of proteins, refolding of misfolded proteins, and also degradation of misfolded and damaged proteins are involved in the protein quality control (PQC) system. Correct protein folding and degradation are controlled by many different factors, one of the most important of which is the heat shock protein family. Heat shock proteins (HSPs) are in the class of molecular chaperones, which may prevent the inappropriate interaction of proteins and induce correct folding. On the other hand, these proteins play significant roles in the degradation pathways, including endoplasmic reticulum-associated degradation (ERAD), the ubiquitin-proteasome system, and autophagy. This review focuses on the emerging role of HSPs in the regulation of protein turnover; the effects of HSPs on the degradation machineries ERAD, autophagy, and proteasome; as well as the role of posttranslational modifications in the PQC system. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: Heat shock proteins; Protein turnover; Proteasome; Autophagy; Protein quality system; Posttranslational modifications; Free radicals; UBIQUITIN-PROTEASOME SYSTEM; CHAPERONE-MEDIATED AUTOPHAGY; HSP90 INHIBITOR GELDANAMYCIN; BCL-X-L; TETHERED MOLECULAR CHAPERONES; STARVATION-INDUCED AUTOPHAGY; ALPHA-B-CRYSTALLIN; I-KAPPA-B; QUALITY-CONTROL; ENDOPLASMIC-RETICULUM